Pengaruh Literasi Budaya Terhadap Kemampuan Penyesuaian Diri Mahasiswa Perantau Yang Tinggal Di Kos Di Kota Medan - Herman Jaya Waruwu; Fransiska Margaretha Tambunan; Bonario Laurensius Sihaloho (Didakta Nusantara: Journal of Education and Learning, 2026)
Students living in boarding houses in Medan City are faced with social and cultural conditions that are different from their hometowns. These differences require good adjustment skills so that students can adapt socially, academically, and emotionally. One factor that is thought to influence the adjustment process is cultural literacy. This study aims to determine the effect of cultural literacy on the adaptability of migrant students living in boarding houses in Medan City. This study uses a quantitative approach with a survey method. The research subjects consisted of 50 migrant students living in boarding houses in Medan City, who were selected using purposive sampling. Data collection was conducted through a Google Form-based questionnaire that measured cultural literacy and adaptability. The data obtained were. analyzed using inferential statistical analysis techniques to see the relationship and influence between the two variables. The results of the study indicate that cultural literacy has an influence on the adaptability of migrant students. Students with better cultural literacy tend to have more positive adaptation skills in facing new social and cultural environments. These findings emphasize the importance of strengthening cultural literacy as a strategy in helping migrant students adapt to urban environments.